Infantile hemangioma/Congenital hemangioma - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Despite the significant clinical evolutionary differences between the common infantile hemangioma (IH) and congenital hemangioma (CH), the latter was identified only 20 years ago. It is important to differentiate CH from IH because their clinical course and their therapy are significantly different.